COVID-19 Pandemic: The Causative Agent is New, The Problem is Old - Igor Klepikov (International Journal of Coronaviruses, 2021)
A perspective situates SARS-CoV-2 within longstanding public health challenges, emphasizing preparedness, surveillance, and the recurrent lessons of outbreak management with examples for practice.
Keywords: pneumonia